APPLICATION OF THE LIABILITY PRINCIPLE IN THE LAND SALE AS JOINT PROPERTY BEFORE A NOTARY - I Komang Wisnu Adi Bujangga; I Wayan Novy Purwanto (Transpublika Publisher, 2022)
This study aims to comprehend the legal basis for selling land as joint property before a notary as well as to know and comprehend the application on principle liability as joint property before a notary. An empiric legal research approach was applied for this study. This study uses statutory approach and fact approach. In this study, primary data was sourced from interviews and secondary data came from the civil code, marriage law, literature, journals and the internet. Data processing is done by qualitative descriptive. The findings of this research indicate that a clause that prohibits the sale of land from joint property without the approval of the wife is incorporated in the agreement that governs the sale of land as joint property. In this case, the liability principle is applied in accordance with the agreement made by the husband as the seller of the land with the buyer. The husband was to blame for the agreement since he neglected to involve his wife in the business transaction involving the land seller. Therefore, according to the principle of liability, responsibility must fall on the shoulders of the seller.